2004
DOI: 10.1038/sj.bjc.6601784
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of capecitabine in combination with paclitaxel in patients with anthracycline-pretreated advanced/metastatic breast cancer

Abstract: The addition of oral capecitabine to docetaxel improves response rate, time to progression (TTP) and overall survival in anthracycline-pretreated metastatic breast cancer (MBC). This phase II study evaluates the efficacy and safety of a 21-day cycle of oral capecitabine (1000 mg m À2 twice daily, days 1 -14) plus i.v. paclitaxel (175 mg m À2 , day 1) in anthracycline-pretreated advanced/ MBC. In all, 73 patients were enrolled at 13 Swedish and Spanish centres. The objective response rate was 52% (95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 27 publications
(27 reference statements)
3
36
0
Order By: Relevance
“…There was no febrile neutropaenia and treatment-related death with TX regimen, while there was 6.7 -9.3% of febrile neutropaenia with ECF, ECX, EOF, and EOX regimen in REAL-2 trial. Two trials of paclitaxel/capecitabine combination in patients with metastatic breast cancer (MBC) showed similar toxicities with asthenia, alopecia, and hand -foot syndrome being common (Batista et al, 2004;Gradishar et al, 2004). Although we found that the incidence of grade 3 or 4 hand -foot syndrome and neuropathy were similar in MBC and AGC patients, grade 3 or 4 neutropaenia was lower in MBC (12 and 15%) than in AGC (46.5%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…There was no febrile neutropaenia and treatment-related death with TX regimen, while there was 6.7 -9.3% of febrile neutropaenia with ECF, ECX, EOF, and EOX regimen in REAL-2 trial. Two trials of paclitaxel/capecitabine combination in patients with metastatic breast cancer (MBC) showed similar toxicities with asthenia, alopecia, and hand -foot syndrome being common (Batista et al, 2004;Gradishar et al, 2004). Although we found that the incidence of grade 3 or 4 hand -foot syndrome and neuropathy were similar in MBC and AGC patients, grade 3 or 4 neutropaenia was lower in MBC (12 and 15%) than in AGC (46.5%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Presuming a biological synergy between epirubicin and paclitaxel and the prodrug capecitabine, an addition of this drug would be expected to improve the efficacy of the treatment. Previously presented phase II data, either with a similar three-drug combination using docetaxel [8], or paclitaxel with capecitabine in patients pretreated with an anthracycline [7] showed promising results, but a randomized phase III trial comparing a combination of docetaxel and epirubicin alone or together with capecitabine failed to show a significant prolongation of PFS [9]. In the present study, the observed PFS exceeded the anticipated time period, which altered the power of the study to reveal a minor difference between the study arms.…”
Section: Safetymentioning
confidence: 99%
“…A phase II trial on the combination of capecitabine with paclitaxel in patients pretreated with anthracycline showed promising results in terms of objective response and time to progression [7]. High response rates were also reported from a phase II trial evaluating the combination of epirubicin, capecitabine and docetaxel [8].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, capecitabine plus 3-weekly or weekly paclitaxel (XP) has also demonstrated high activity in firstline MBC (Table 2), including response rates in the range of 40%-73% and an overall survival time of up to almost 30 months [52][53][54][55][56]. This combination has a favorable safety profile with a low incidence of grade 3 or 4 adverse events.…”
Section: Expanding Treatment Options With Capecitabine-taxane Combinamentioning
confidence: 99%